Clinical correlation of retinal nerve fiber layer thickness in multiple sclerosis patients- A North Indian study - Upasana Patel; Hilal Ahmad Sheikh; C. S. Agrawal; A. Rohatgi; A. K. Grover (International Journal of Medical Research and Review, 2019)
Background: Axonal loss is thought to occur early in the course multiple sclerosis (MS) and is supposed to be associated with, and predictive of, neurologic deficits progressing to permanent disability.Axonal loss in the retinal nerve fiber layer (RNFL) is measured by optical coherence tomography (OCT).Material and Methods: A longitudinal observational study, conducted on 30 MS patients. All subjects underwent neurological examination, including expanded disability status scale (EDSS) scoring and OCT on two visits, minimum 2 months apart.Results: Total of 60 eyes of 30 patients were subdivided into 21 eyes having optic neuritis (ON) [‘MS – ON’] and 39 eyes without ON. The RNFL thickness (RNFLt) was found to be significantly reduced in all parameters except in temporal quadrant, as the duration of disease increases. Average RNFLt were found to have negative correlation (r = -0.450) with disease duration. Negative correlation (r=-0.657) was also found between EDSS score change and average RNFLt change. The eyes having ON showed statistically significant RNFL thinning as compared to the non – ON fellow eyes. The baseline EDSS score was found to be negatively correlated (moderate degree, r = -0.348) with baseline average RNFL thickness, with p-value of 0.006.Conclusions: The RNFLt is not only significantly thinner in those with history of ON, but it is also affected remarkably even in absence of prior ON, suggesting subclinical ongoing axonal loss in patients with MS. The EDSS score is inversely correlated with RNFL thickness.